Correlation of Barrett's esophagus with colorectal polyps in Japanese patients: A retrospective chart review. Issue 7 (19th February 2019) - Takedomi, Hironobu; Tsuruoka, Nanae; Takamori, Ayako; Miyahara, Koichi; Yamanouchi, Kohei; Shimamura, Takuya; Fujimoto, Yo; Noda, Takahiro; Matsunaga, Takuya; Takara, Yoshimichi; Shimada, Furitsu; Hidaka, Hidenori; et al.
Abstract: Background and Aim: Barrett's esophagus and colorectal polyps have several overlapping risk factors. Whereas several reports in Western countries have indicated a close relationship between Barrett's esophagus and colorectal polyps, the relationship between these two diseases remains unclear in Japan. This study was performed to determine whether the prevalence of Barrett's esophagus is related to that of colorectal polyps in Japanese patients. Methods: The present retrospective chart review included 1582 Japanese patients who underwent both total colonoscopy and esophagogastroduodenoscopy from January 2010 to December 2016. The data on colorectal polyps and Barrett's esophagus were obtained from the endoscopic findings. The medical record of each patient was checked for age, sex, body mass index, smoking, alcohol drinking, use of acid suppression agents, and comorbidities including a history of diabetes, ischemic heart disease, gastroesophageal reflux disease, hiatal hernia, and Helicobacter pylori infection. Results: Colorectal polyps were detected in 789 of the 1582 patients (49.9%). Barrett's esophagus was detected in 233 patients (14.7%), and most cases of Barrett's esophagus ( n = 229) were classified as short‐segment Barrett's esophagus. Colorectal polyps were more frequent in patients with than without Barrett's esophagus (odds ratio, 1.79; 95% confidence interval, 1.31–2.46; P < 0.001). In addition to Barrett's esophagus, the data indicated that old age, male sex, obesity, smoking, alcohol drinking, diabetes mellitus, and ischemic heart disease were independent risk factors for colorectal polyps. Conclusions: The present study revealed the correlation between the prevalence of Barrett's esophagus and colorectal polyps in Japanese patients.